Study of human knowledge and attitude toward urban birds in Faisalabad city, Pakistan - Nawaz,M. F. (2023)
Abstract Birds are very valuable indicators of species richness and endemic patterns in a specified ecosystem, which eventually help the scientist to measure the environmental degradation. The aim of present study was to know human knowledge and attitude toward urban birds in Faisalabad city, Pakistan. The study conducted in four consecutive months: November 2019 to February 2020. Population of birds was noted from eight residential towns of Faisalabad city, data were collected through questionnaire. Faisalabad has a reasonably large population of birds and present data show that, there is a significant difference between favorite bird of residential areas and institutions. The pigeon received the most likeness in bird population among residential area residents, while the myna received the least. The most popular bird in Faisalabad institutions was the sparrow, while the least popular bird was the common myna. Bird adaptation percentage of residential areas and institutional areas of Faisalabad was the highest for parrot and sparrow respectively. People in residential areas and institutions, on the other hand, adapted least to common myna. It is concluded that people of the study area like birds and offered food and high population of birds are present in study area.